Photolysis of Some Pyrimidines by UV Light: Part I - Singh Chawada, Shivraj; Jain, Shubha (Asian Journal of Chemistry, 2010)
Pyrimidines, viz., thymine, cytosine and uracil when photolysed by UV light, gave the dimer (II) and dewar-2-pyrirnidones (IV) and (VI) respectively. The structures of these products have been established by spectral and elemental analysis.